Emperor penguin diorama - Field Museum of Natural History (2023)
Emperor Penguin diorama with multiple mounted specimens and a painted background depicting a scene from the Ross Ice Shelf in Antarctica. The specimens were collected at Little America, the principal American base in Antarctica, by the Second Byrd Antarctic Expedition in 1935. Sugar was originally used to simulate snow but was replaced in the 1980s when pests were discovered infesting the exhibit cases.